Sintered body and parts containing it

JP7638345B2Active Publication Date: 2025-03-03SOLMICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023176312
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-11-15
Filing Date
2023-10-11
Publication Date
2025-03-03
Estimated Expiration
2043-10-11

AI Technical Summary

Benefits of technology

【0020】 具現例に係る焼結体は、高い緻密化度、低い気孔率を有し、均一な結晶粒サイズ分布を有することで、良好な物理的特性を示すことができ、優れたプラズマ耐エッチング性を確保することができる。また、プラズマ耐エッチング性を安定的に維持することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638345000009
    Figure 0007638345000009
  • Figure 0007638345000010
    Figure 0007638345000010
  • Figure 0007638345000011
    Figure 0007638345000011
Patent Text Reader

Abstract

To provide a sintered body and a component containing the same that can induce substantially uniform plasma distribution on an etching target and has improved plasma etching resistance.SOLUTION: A sintered body contains boron carbide, and when observed on the surface, includes a portion in which the volume ratio of crystal grains having a crystal grain size of more than 1 μm and not more than 4 μm to all crystal grains is 61% to 86%. According to X-ray fluorescence analysis, the carbon content is 18 to 30 weight%, and the porosity is 5 volume% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Embodiments relate to a sintered body having improved plasma etching resistance, and a part of a plasma processing apparatus including the same. [Background technology]

[0002] A plasma processing apparatus has an upper electrode and a lower electrode arranged inside a chamber, a semiconductor wafer, a glass substrate, etc., placed on the lower electrode, and operates by applying power between the two electrodes. Electrons accelerated by the electric field between the upper electrode and the lower electrode, electrons emitted from the electrodes, or heated electrons ionize and collide with molecules of the processing gas to generate plasma of the processing gas. Active species such as radicals and ions in this plasma can realize the desired microfabrication of the surface of the etching target, for example, etching processing.

[0003] As manufacturing designs for electronic devices become increasingly miniaturized, higher dimensional accuracy is required, especially in plasma etching, and significantly higher power is used. Such plasma processing equipment has a built-in focus ring that is affected by the plasma.

[0004] When the plasma power becomes high, a wavelength effect in which a standing wave is formed, a skin effect in which the electric field is concentrated in the center of the electrode surface, etc. may be formed, and as a result, the plasma distribution is generally maximized in the center of the etching target and is lowest at the edge, which may cause the plasma distribution on the substrate to become significantly non-uniform, and may result in a deterioration in the quality of the microelectronic device.

[0005] The focus ring, which places the etching target on the outer periphery of the etching target, can affect the electric field distribution of the outer periphery, thereby alleviating non-uniformity of plasma distribution to some extent. However, the etching rate of the focus ring is relatively high compared to the plasma processing time, and the etching can affect the plasma distribution. There is a need for an improvement that can improve the etching resistance and replacement cycle of the focus ring and achieve process efficiency.

[0006] The above-mentioned background art is technical information that the inventor possessed for the purpose of deriving the embodiments or that he / she acquired in the process of deriving the embodiments, and is not necessarily publicly known art that was disclosed to the general public prior to the filing of the application of the present invention.

[0007] Related prior art includes the "boron carbide material" disclosed in Korean Patent Registration No. 10-2262340 and the "boron carbide sintered body and etching apparatus including the same" disclosed in Korean Patent Publication No. 10-2020-0019068. Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the embodiment is to provide a sintered body capable of inducing a substantially uniform plasma distribution on an etching target and having improved plasma etching resistance, and a part including the same. [Means for solving the problem]

[0009] In order to achieve the above object, the sintered body according to the embodiment is The material may contain boron carbide, and when observed on the surface, the volume ratio of crystal grains having a crystal grain size of more than 1 μm and not more than 4 μm to all crystal grains may be 61% to 86%, and the carbon content based on X-ray fluorescence analysis may be 18% to 30% by weight, and the porosity may be 5% by volume or less.

[0010] In an embodiment, the sintered body may have a volume ratio of crystal grains having a crystal grain size of 1 μm or less to the total crystal grains of 1.5% to 15%.

[0011] In an embodiment, the sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 4 μm of 7.2% to 31% of all crystal grains.

[0012] In an embodiment, the sintered body may have an average crystal grain size of 2 μm to 5 μm.

[0013] In an embodiment, the sintered body may have a porosity of 0.5 vol% or less and a boron and carbon content of 97 wt% or more.

[0014] In one embodiment, the sintered body is formed by CF in the chamber at a chamber pressure of 100 mTorr, a plasma power of 800 W, and an exposure time of 300 minutes. 4 The gas flow rate was 50 sccm, Ar gas flow rate was 100 sccm, and O 2 Under plasma etching conditions where the gas flow rate is 20 sccm, the etching rate according to the following formula 1 may be 2% or less.

[0015] [Formula 1] Etching rate = {(thickness before etching - thickness after etching) / (thickness after etching)} x 100%

[0016] In an embodiment, the sintered body may have a thermal conductivity of 18 W / mK to 33 W / mK at 25° C.

[0017] In order to achieve the above object, a method for producing a sintered body according to an embodiment includes the steps of: a carbonization step in which the raw material composition is charged into a mold, molded, and heat-treated at a temperature of 500°C to 1000°C; After the carbonization step, a first sintering step of heat treating at a temperature of 1900°C to 2100°C; After the first sintering step, a second sintering step of heat treating at a temperature of 2000°C to 2230°C is included, The raw material composition includes boron carbide and a sintering property improver, The first sintering step and the second sintering step may be carried out at a pressure of 25 MPa to 60 MPa.

[0018] In an embodiment, the raw material composition may be raw material granules obtained by spray drying a raw material slurry including boron carbide, a sintering property improver, and a solvent.

[0019] In order to achieve the above object, the part according to the embodiment includes: The sintered body may be included and may be applied to the inside of a plasma processing apparatus. Effect of the Invention

[0020] The sintered body according to the embodiment has a high degree of densification, low porosity, and uniform grain size distribution, and therefore exhibits good physical properties and can ensure excellent plasma etching resistance, and can stably maintain the plasma etching resistance. [Brief description of the drawings]

[0021] [Figure 1] (a) shows the surface of the sintered body of Example 1 before electrolytic etching, (b) shows the surface of the sintered body of Example 1 after electrolytic etching, and (c) shows identifiable crystal grains on the surface of the sintered body of Example 1 after electrolytic etching, differentiated by color. [Diagram 2] (a) shows the surface of the sintered body of Example 3 before electrolytic etching, (b) shows the surface of the sintered body of Example 3 after electrolytic etching, and (c) shows identifiable crystal grains on the surface of the sintered body of Example 3 after electrolytic etching, differentiated by color. [Diagram 3] Photographs (a) to (c) are images of the samples of Examples 1 to 3 after plasma etching, respectively, and (d) is an image of the sample of Comparative Example 1 after plasma etching. [Figure 4](a) shows the surface of the sintered body of Example 1 and the measurement positions of the composition before electrolytic etching, and (b) shows the surface of the sintered body of Example 1 and the measurement positions of the composition after electrolytic etching. [Diagram 5] (a) shows the surface of the sintered body of Example 3 and the measurement positions of the composition before electrolytic etching, and (b) shows the surface of the sintered body of Example 3 and the measurement positions of the composition after electrolytic etching. [Figure 6] (a) to (c) respectively show the surface states before plasma etching in Examples 1 to 3, and (d) to (f) respectively show the surface states after plasma etching in Examples 1 to 3. [Figure 7] 1(a) shows the surface state of Comparative Example 1 before plasma etching, and FIG. 1(b) shows the surface state of Comparative Example 1 after plasma etching. BEST MODE FOR CARRYING OUT THEINVENTION

[0022] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS One or more exemplary embodiments will now be described in detail with reference to the accompanying drawings in order to enable those of ordinary skill in the art to easily make and use the present invention. However, the exemplary embodiments may be embodied in many different forms and are not limited to the embodiments set forth herein. Like reference numerals are used throughout the specification to refer to like parts.

[0023] In this specification, when a certain configuration "includes" another configuration, this does not mean to exclude the other configurations, unless specifically stated to the contrary, but rather means that the other configurations may also be included.

[0024] In this specification, when a certain component is said to be "connected" to another component, this includes not only the case where the component is "directly connected" but also the case where the component is "connected via another component between them."

[0025] In this specification, the term "B is located on A" means that B is located on A in direct contact therewith, or that B is located on A with another layer located therebetween, and is not to be interpreted as being limited to B being located in contact with the surface of A.

[0026] As used herein, the term "combinations thereof" contained in a Markush form expression means a mixture or combination of one or more selected from the group of components set forth in the Markush form expression, and is meant to include one or more selected from the group of components.

[0027] In this specification, the phrase "A and / or B" means "A, B, or A and B."

[0028] In this specification, terms such as "first", "second" or "A", "B" are used to distinguish identical terms from each other, unless otherwise specified.

[0029] In this specification, the term "singular" is to be construed as including the singular or plural as the context requires, unless otherwise specified.

[0030] Sintered body In order to achieve the above object, the sintered body according to the embodiment is Contains boron carbide, When observed on the surface, the volume ratio of crystal grains with a crystal grain size of more than 1 μm and less than 4 μm to the total crystal grains is 61% to 86%, The carbon content based on the total weight may be 18% to 30% by weight as determined by X-ray fluorescence analysis.

[0031] The boron carbide of the sintered body is substantially 4 It may also be C.

[0032] The sintered body may further contain some silicon, oxygen, boron oxide, etc., based on boron carbide. Substances other than boron carbide in the sintered body may be present in the form of a secondary phase.

[0033] The sintered body may include boron carbide grains, which may also be observed at the surface of the sintered body.

[0034] Although the sintered body is manufactured through pressure sintering, it can have a crystal grain size controlled to a certain level.

[0035] The sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 1 μm and not more than 4 μm to all crystal grains of 61% to 86%, or 63% to 83%.

[0036] The sintered body may have a volume ratio of crystal grains having a crystal grain size of 1 μm or less to all crystal grains of 1.5% to 15%, or 2% to 13.8%.

[0037] The sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 4 μm to all crystal grains of 7.2% to 31%, or 10.2% to 29%.

[0038] The sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 4 μm and not more than 5 μm to all crystal grains of 25% to 43.8%, or 27% to 41.8%.

[0039] The sintered body may have a volume ratio of crystal grains having a crystal grain size of more than 5 μm to all crystal grains of 7.7% to 12.5%, or 8.7% to 10.6%.

[0040] The sintered body may have a porosity controlled to 0.5 volume % or less, or a relative density controlled to 99.5% or more, and the volume ratio of crystal grains having a crystal grain size of more than 1 μm and 4 μm or less to the total crystal grains may be 61% to 86%, or 63% to 83%.

[0041] The sintered body may have a porosity controlled to 0.5 volume % or less, or a relative density controlled to 99.5% or more, and the volume ratio of crystal grains having a crystal grain size of 1 μm or less to the total crystal grains may be 0.5% to 4.5%, or may be 1% to 4%.

[0042] The sintered body may have a porosity controlled to 0.5 volume % or less, or a relative density controlled to 99.5% or more, and the volume ratio of crystal grains having a crystal grain size of more than 4 μm to the total crystal grains may be 20.8% to 31.3%, or 23.5% to 28.7%.

[0043] The sintered body may have a porosity controlled to 0.5 volume % or less, or a relative density controlled to 99.5% or more, and the volume ratio of crystal grains having a crystal grain size of more than 4 μm and 5 μm or less to the total crystal grains may be 13.1% to 19.7%, or 14.8% to 18%.

[0044] The sintered body may have a porosity controlled to 0.5 volume % or less, or a relative density controlled to 99.5% or more, and the volume ratio of crystal grains having a crystal grain size of more than 5 μm to the total crystal grains may be 5% to 13%, or 7.7% to 11.6%.

[0045] The sintered body may have an average crystal grain size of 1 μm to 5 μm, or 1.5 μm to 4.5 μm.

[0046] The grain size of the sintered body can be analyzed by the method described in the following experimental examples, and can be based on that observed on the surface.

[0047] The sintered body having such characteristics has a high degree of densification, low porosity, and a uniform crystal grain size distribution, and therefore exhibits good physical properties and can ensure excellent plasma etching resistance. In addition, the plasma etching resistance can be stably maintained.

[0048] The sintered body may have a purity of 97% or more, or 98.1% or more, based on boron and carbon (B, C).

[0049] The purity is assessed on a weight basis by X-ray fluorescence analysis (XRF).

[0050] The sintered body may have a carbon content of 18% by weight to 30% by weight, or 19% by weight to 28% by weight, based on the total weight, as determined by X-ray fluorescence analysis (XRF). 4 C) may contain no additional carbon in the stoichiometric carbon content.

[0051] The sintered body may have a boron content of 70% by weight to 80% by weight, or 73% by weight to 79% by weight, based on the total weight, as determined by X-ray fluorescence analysis.

[0052] The sintered body may have an oxygen content of 0.1% by weight to 1.2% by weight, or 0.2% by weight to 1% by weight, based on the total weight, as determined by X-ray fluorescence analysis.

[0053] The sintered body may have a silicon content of 0.1% by weight to 1% by weight, or 0.2% by weight to 0.8% by weight, based on the total weight, as determined by X-ray fluorescence analysis.

[0054] The sintered body can be further densified by containing such other elements.

[0055] The sintered body may contain metallic impurities of 400 ppm or less, or 200 ppm or less. The metallic impurities may include sodium, aluminum, calcium, iron, nickel, etc.

[0056] The flexural strength of the sintered body may be 381 MPa to 571 MPa, or 428 MPa to 524 MPa.

[0057] The sintered body may have a Vickers hardness of 26 GPa to 39 GPa, or 29 GPa to 36 GPa.

[0058] The sintered body may have a thermal conductivity of 18.4 W / mK to 27.6 W / mK, or may have a thermal conductivity of 21 W / mK to 25 W / mK.

[0059] A sintered body having such characteristics can exhibit good reliability and durability when applied to parts of a plasma processing apparatus, and can be useful in maintaining plasma etching resistance.

[0060] The sintered body was prepared by subjecting the chamber pressure to 100 mTorr, plasma power to 800 W, plasma exposure time to 300 minutes, and CF 4 The gas flow rate was 50 sccm, Ar gas flow rate was 100 sccm, and O 2 Under plasma etching conditions where the gas flow rate is 20 sccm, the etching rate according to the following formula 1 may be 2% or less.

[0061] [Formula 1] Etching rate = {(thickness before etching - thickness after etching) / (thickness after etching)} x 100%

[0062] The etching rate of the sintered body may be 2% or less, 1.7% or less, 1.45% or less, or 1.4% or less. The etching rate may be 0.1% or more.

[0063] The sintered body has such plasma etching resistance and also has the characteristic of large crystal grains, so that generation of particles during the plasma processing step can be suppressed to the maximum extent.

[0064] The sintered body may have an etching rate that is reduced by 20% or more, or may have an etching rate that is reduced by 32% or more, based on the plasma etching conditions, compared to the etching rate of silicon carbide formed by chemical vapor deposition (CVD).

[0065] The sintered body may have a relative density of 95% or more, 97% or more, or 99% or more. The relative density may be 99.9% or less. The sintered body may exhibit relatively uniform and controlled grain size and have excellent relative density. The relative density is expressed as a percentage of the relative density of the sintered body, with a completely dense state being 100%.

[0066] parts In order to achieve the above object, the part according to the embodiment comprises: The sintered body includes It can be applied inside a plasma processing apparatus.

[0067] The part may include the sintered body on only a portion or on the entire surface that may be exposed to plasma.

[0068] The part may include the sintered body on a surface thereof, and the interior of the surface may include other ceramic materials (eg, silicon carbide, silicon, etc.).

[0069] The component may be a component capable of affecting a flow of plasma ions during a plasma etching process, and may be, for example, a focus ring, etc. The focus ring may be used as a support for supporting an edge of a wafer when the wafer is placed in a plasma processing apparatus.

[0070] By including the sintered body, the part can ensure good plasma etching resistance, reduce the frequency of part replacement, and effectively prevent the generation of particles that may negatively affect yield.

[0071] Manufacturing method of sintered body In order to achieve the above object, a method for producing a sintered body according to an embodiment includes: a carbonization step in which the raw material composition is charged into a mold, molded, and heat-treated at a temperature of 500°C to 1000°C; After the carbonization step, a first sintering step of heat treating at a temperature of 1900°C to 2100°C; After the first sintering step, a second sintering step of heat treating at a temperature of 2000°C to 2230°C is included, The raw material composition includes boron carbide and a sintering property improver, The first sintering step and the second sintering step may be carried out at a pressure of 25 MPa to 60 MPa.

[0072] The raw material composition may be raw material granules obtained by spray drying a raw material slurry containing boron carbide, a sintering characteristic improver, and a solvent.

[0073] The boron carbide in the raw material composition may be in the form of a powder, and may be a powder having a purity of 98% by weight or more of boron and carbon based on the entire powder.

[0074] The raw material composition may further include a separate carbon-based material, which may be a polymer resin or a carbonized form of the polymer resin, such as a phenol-based resin or a polyvinyl alcohol-based resin.

[0075] The sintering characteristic improver of the raw material composition may include boron oxide, a binder, etc., and the binder may include an acrylic resin.

[0076] The solvent of the raw material composition may include water, an alcohol-based substance, etc., and may be included in an amount of 60% by volume to 80% by volume based on the entire raw material slurry.

[0077] The raw material slurry may be prepared through an agitation process using a ball mill or the like, and the ball mill agitation process may be carried out using polymer balls or the like for 5 to 20 hours.

[0078] The green body can be obtained by injecting the raw material into a mold and applying pressure, for example, cold isostatic pressing (CIP), etc. In this case, the pressure may be 100 MPa to 200 MPa.

[0079] The molded body may be subjected to a processing step for removing unnecessary parts.

[0080] The temperature of the first sintering step may be 1900°C to 2100°C, or 1950°C to 2050°C.

[0081] The temperature of the second sintering step may be 2000°C to 2230°C, or 2080°C to 2180°C.

[0082] The temperature of the second sintering step may be higher than that of the first sintering step, and by applying such a temperature, a sintered body having more uniform grain characteristics and mechanical properties may be obtained.

[0083] The temperature rise to the heat treatment temperature in the first sintering step may be carried out for 10 to 15 hours.

[0084] The first sintering step may be carried out for 0.5 to 2 hours.

[0085] The temperature rise to the heat treatment temperature in the second sintering step may be carried out for 2 hours to 5 hours.

[0086] The second sintering step may be carried out for 0.5 to 3 hours.

[0087] After the second sintering step, a cooling step of cooling to room temperature may be performed, and may be performed for 10 to 15 hours.

[0088] Through this sintering step, a sintered body having uniform and controlled crystal grains can be produced, and a good degree of densification can be achieved.

[0089] The sintered body obtained through the second sintering step may be subjected to additional shaping.

[0090] In the first sintering step, a predetermined heating rate may be applied until the heat treatment temperature is reached, and the heating rate may be 1°C / min to 10°C / min, or 2°C / min to 5°C / min.

[0091] In the second sintering step, a predetermined heating rate may be applied until the heat treatment temperature is reached, and the heating rate may be 0.1°C / min to 5°C / min, or 0.2°C / min to 1°C / min.

[0092] After the second sintering step, a predetermined temperature drop rate may be applied in a cooling step, and the temperature drop rate may be -10°C / min to -1°C / min, or may be -5°C / min to -2°C / min.

[0093] The first sintering step and the second sintering step may be performed at a pressure of 25 MPa to 60 MPa, or at a pressure of 30 MPa to 50 MPa. In this case, the pressure of the second sintering step may be higher than the pressure of the first sintering step. By applying such pressure, a good degree of densification of the sintered body can be obtained.

[0094] The present invention will be described in more detail with reference to the following specific examples. The following examples are merely illustrative for the purpose of aiding understanding of the present invention, and are not intended to limit the scope of the present invention.

[0095] Example 1 - Production of sintered body 1 A composition obtained by mixing 14 parts by volume of boron carbide powder from China Abrasive and 70 parts by volume of ethanol solvent for a total of 100 parts by volume of the mixture of the powder and the solvent with 2 parts by weight of an acrylic binder was placed in a compounder and mixed by a ball mill method to produce a raw material slurry. The raw material slurry was spray-dried through a nozzle to obtain raw material granules, and the raw material granules were filled into a carbon mold of a pressure sintering device. The carbon mold filled with the raw material granules was heat-treated at a temperature of 800°C to perform a carbonization step. After that, the first sintering step was performed in which the temperature was raised to 1900°C at a heating rate of 3°C / min, and then heat-treated at 1900°C and a pressure of 30MPa for 1 hour. After that, the second sintering step was performed in which the temperature was raised to 2000°C at a heating rate of 0.5°C / min, and then heat-treated at 2000°C and a pressure of 35MPa for 0.5 hours. Thereafter, a cooling step was performed to cool the mixture to room temperature (25° C.) at a rate of 3° C. / min to produce a sintered body with a relative density of 95%.

[0096] Example 2 - Production of sintered body 2 In Example 1, the conditions of the second sintering step were changed to 2100° C., 35 MPa, and 1 hour, to produce a sintered body with a relative density of 97%.

[0097] Example 3 - Production of sintered body 3 In Example 1, the conditions of the second sintering step were changed to 2130° C., 40 MPa, and 1.5 hours to produce a sintered body with a relative density of 99.9%.

[0098] Comparative Example 1 - Manufactured by chemical vapor deposition Silicon carbide manufactured by chemical vapor deposition (CVD) from KNJ was prepared.

[0099] The examples and comparative examples are briefly shown in Table 1.

[0100] [Table 1]

[0101] Experimental example - Analysis of crystal grains and composition through electrolytic etching of sintered body The sintered body produced in Example 3 was subjected to electrolytic etching under the conditions of 2% by volume KOH solution, 12-20sccm flow rate, 5 seconds, and 40-51V voltage, followed by ultrasonic cleaning for 20 minutes. The surface before and after electrolytic etching was photographed at 5000x magnification at three arbitrary regions of the surface using a scanning electron microscope (SEM), and the volume ratio of each crystal grain size was analyzed, and the composition at some positions (A, B, C, D, E) before and after electrolytic etching was analyzed, and the results are shown in Figures 1, 2, 4, 5, Tables 2 to 6, etc.

[0102] [Table 2]

[0103] [Table 3]

[0104] [Table 4]

[0105] [Table 5]

[0106] [Table 6]

[0107] Fig. 1(a) shows the surface of the sintered body of Example 1 before electrolytic etching, Fig. 1(b) shows the surface of the sintered body of Example 1 after electrolytic etching, and Fig. 1(c) shows the identifiable crystal grains on the surface of the sintered body of Example 1 after electrolytic etching, distinguished by color. Red indicates 1 μm or less, yellow-green indicates more than 1 μm and less than 2 μm, blue indicates more than 2 μm and less than 3 μm, yellow indicates more than 3 μm and less than 4 μm, sky blue indicates more than 4 μm and less than 5 μm, and purple indicates more than 5 μm and less than 6 μm.

[0108] Fig. 2(a) shows the surface of the sintered body of Example 3 before electrolytic etching, Fig. 2(b) shows the surface of the sintered body of Example 3 after electrolytic etching, and Fig. 2(c) shows identifiable crystal grains on the surface of the sintered body of Example 3 after electrolytic etching, distinguished by color. The color classification is the same as the above-mentioned conditions.

[0109] FIG. 4(a) shows the surface of the sintered body of Example 1 and the measurement positions of the composition before electrolytic etching, and FIG. 4(b) shows the surface of the sintered body of Example 1 and the measurement positions of the composition after electrolytic etching.

[0110] FIG. 5(a) shows the surface of the sintered body of Example 3 and the measurement positions of the composition before electrolytic etching, and FIG. 5(b) shows the surface of the sintered body of Example 3 and the measurement positions of the composition after electrolytic etching.

[0111] Referring to Table 2 and FIGS. 1 and 2(a) to (c), it was confirmed that the sintered bodies of Examples 1 and 3 had crystal grains of several μm uniformly distributed, and had almost no crystal grains having a size exceeding 6 μm or less than 1 μm.

[0112] With reference to Tables 3 to 6, FIGS. 4(a) to (c), and FIGS. 5(a) to (c), in the sintered body of Example 1, not only boron carbide but also some oxygen, silicon, tin, etc. can be confirmed on the surface before and after electrolytic etching, and in the sintered body of Example 3, not only boron carbide but also silicon, etc. can be confirmed.

[0113] Experimental example - X-ray fluorescence analysis (XRF) X-ray fluorescence spectroscopy (XRF) of the samples of Example 3 and Comparative Example 1 was performed using a Rigaku ZSX Primus instrument, and the results are shown in Table 7.

[0114] [Table 7]

[0115] Referring to Table 7, it can be seen that the sintered body of Example 3 contains approximately 78.1% by weight of boron, 20.1% by weight of carbon, and some oxygen, silicon, and the like.

[0116] Experimental Example - Plasma Etching Rate Measurement The plasma etching rates of the sintered body samples of Examples 1 to 3 and Comparative Example 1 were measured under the following conditions, and the results are shown in Table 8, FIG. 3, FIG. 6, FIG.

[0117] Plasma etching conditions Chamber pressure: 100 mTorr, plasma power: 800 W, exposure time: 300 min, CF 4 Gas flow rate: 50 sccm, Ar gas flow rate: 100 sccm, O 2 Gas flow rate: 20sccm

[0118] 3(a) to (c) are photographs of the samples of Examples 1 to 3, respectively, after plasma etching, and FIG. 3(d) is a photograph of the sample of Comparative Example 1 after plasma etching.

[0119] 6(a) to (c) show the surface conditions before plasma etching for Examples 1 to 3, respectively, and FIGS. 6(d) to (f) show the surface conditions after plasma etching for Examples 1 to 3, respectively.

[0120] FIG. 7(a) shows the surface state of Comparative Example 1 before plasma etching, and FIG. 7(b) shows the surface state of Comparative Example 1 after plasma etching.

[0121] [Table 8] *Etching rate: {(thickness before etching - thickness after etching) / (thickness after etching)} x 100%

[0122] Referring to Table 8, it can be seen that in Examples 1 to 3, the silicon carbide has better plasma etching resistance than silicon carbide produced by CVD.

[0123] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the appended claims also fall within the scope of the present invention.

Claims

1. Contains boron carbide, When observed on the surface, the volume ratio of crystal grains having a crystal grain size of more than 1 μm and not more than 4 μm to the total crystal grains is 61% to 86%; The carbon content based on the total weight is 18% to 30% by weight according to X-ray fluorescence analysis; The boron content is 70% to 80% by weight based on the total weight according to X-ray fluorescence analysis; A sintered body having a porosity of 5 volume % or less.

2. 2. The sintered body according to claim 1, wherein the volume ratio of crystal grains having a crystal grain size of 1 μm or less to the total volume of crystal grains is 1.5% to 15%.

3. The sintered body according to claim 1, wherein the volume ratio of crystal grains having a crystal grain size of more than 4 μm to the total volume of crystal grains is 7.2% to 31%.

4. 2. The sintered body according to claim 1, having an average grain size of 2 μm to 5 μm.

5. The porosity is 0.5 vol% or less, 2. The sintered body according to claim 1, wherein the boron and carbon content is 97% by weight or more.

6. The chamber pressure was 100 mTorr, the plasma power was 800 W, the exposure time was 300 minutes, and the CF 4 The gas flow rate is 50 sccm, the Ar gas flow rate is 100 sccm, and O 2 2. The sintered body according to claim 1, wherein under plasma etching conditions with a gas flow rate of 20 sccm, the etching rate according to the following formula 1 is 2% or less. [Formula 1] Etching rate = {(thickness before etching - thickness after etching) / (thickness after etching)} x 100%

7. 2. The sintered body according to claim 1, having a thermal conductivity at 25° C. of 18 W / mK or more and 33 W / mK or less.

8. A method for producing the sintered body of claim 1, comprising the steps of: a carbonization step of charging the raw material composition into a mold, forming the raw material composition, and heat-treating the raw material composition at a temperature of 500° C. to 1000° C.; After the carbonization step, a first sintering step of heat treatment at a temperature of 1900°C to 2100°C; A second sintering step of heat treating the first sintering step at a temperature of 2000°C to 2230°C, The raw material composition includes boron carbide and a sintering property improver, The first sintering step and the second sintering step are carried out at a pressure of 25 MPa to 60 MPa.

9. The raw material composition is The method according to claim 8, wherein the raw material granules are obtained by spray drying a raw material slurry containing boron carbide, a sintering characteristic improver and a solvent.

10. The sintered body according to claim 1, Parts applied inside a plasma processing device.

Citation Information

Patent Citations

  • Ceramic sintered compact

    JP2004196590A

  • Boron carbide sintered compact and method of manufacturing the same

    JP2008133160A

  • Boron carbide sintered body and etcher including the same

    JP2020073420A

  • Ring-shaped element for etcher and method for etching substrate using the same

    US20200051793A1

  • Ceramic component and plasma etching apparatus comprising same

    WO2021162424A1